Effects of Taijiquan and Qigong exercises on depression and anxiety levels in patients with substance use disorders: A systematic review and meta-analysis - Peng Zhang; Zaimin Li; Qing Yang; Jiali Zhou; Xiujie Ma (Sports Medicine and Health Science, 2022)
Previous studies have shown that Taijiquan and Qigong exercise can effectively reduce depression and anxiety in healthy and clinical populations. At present, only a few reviews have elaborated on the premise of different types of interventions, and there is still a lack of studies that systematically summarize the clinical evidence of patients with substance use disorders. The purpose of this meta-analysis was to assess the impact of the Taijiquan and Qigong exercise on the mood of individuals with substance use disorders (SUD); Articles were searched in Pubmed, Embase, Cochrane Library, Web of Science, and CNKI from their inception to the May 24, 2021. All randomized controlled trials (RCT) using Taijiquan and Qigong intervention were included. With the Review Manager software to determine the effect (standardized mean difference, SMD), subgroup analysis was conducted to intervention type, exercise time, and exercise duration. Nine studies totaling 823 participants were included in the study. Overall results indicated that Taijiquan and Qigong exercise had significant benefits in reducing depression (SMD = −0.35, 95% CI: −0.53 to −0.18, Z = 4.00, p < 0.01) and anxiety (SMD = −0.31, 95% CI: −0.50 to −0.11, Z = 3.06, p < 0.01) symptoms in SUD. When depression and anxiety were examined separately, subgroup analysis demonstrated that Taijiquan intervention (SMD = −0.45, 95% CI: −0.71 to −0.19, Z = 3.39, p < 0.01) and Qigong intervention (SMD = −0.28, 95% CI −0.51 to −0.04, Z = 2.33, p = 0.02),30–60 min exercise time (SMD = −0.41, 95% CI: −0.61 to −0.20, Z = 3.82, p < 0.01) and duration of 9–12 weeks (SMD = −0.57, 95% CI: −1.10 to −0.04, Z = 2.10, p = 0.04) more than 12 weeks (SMD = −0.28, 95% CI: −0.50 to −0.07, Z = 2.59, p = 0.01) could effectively alleviate the symptoms of depression. Meanwhile, Qigong intervention (SMD = −0.31, 95% CI: −0.52 to −0.10, Z = 2.85, p < 0.01), 30–60 min exercise time (SMD = −0.29, 95% CI: −0.53 to −0.04, Z = 2.28, p = 0.02), more than 60 min exercise time (SMD = −0.54, 95% CI: −1.06 to −0.02, Z = 2.05, p = 0.04), and duration of less than 9 weeks (SMD = −0.35, 95% CI: −0.68 to −0.02, Z = 2.07, p = 0.04) had positive effects on alleviating anxiety symptoms with SUD. Taijiquan and Qigong exercise could reduce levels of anxiety and depression in those with SUD. Considering the small number of included studies, more reliable RCTs are needed on this topic.